Embedding co-production of nature-based solutions in urban governance: Emerging co-production capacities in three European cities - Collier, Marcus (My University, 2024)
This paper seeks to understand how co-production can become embedded as a collaborative governance practice by which city governments plan, deliver and steward nature-based solutions. To these ends, the paper analyses how policy officers manifest capacities for co-production in three European cities – Genk (Belgium), Glasgow (United Kingdom) and Poznań (Poland) – while experimenting with co-production to develop and scale nature-based solutions. Co-production capacities include conditions and activities to (1) create space for co-production, (2) safeguard inclusive and legitimate co-production, and (3) link co-production processes and results to contexts. The results demonstrate how policy officers in the three cities have mobilised and created resources, skills, institutional support and partnerships to implement diverse processes to co-produce nature-based solutions. While these conditions mark starting changes in urban governance, engaging with and embedding co-production causes tensions between the dynamic and diffuse nature of co-production and existing formal governance settings and processes. Lessons for strengthening the capacities to embed co-production as a collaborative governance practice in nature-based solutions planning, delivery and stewardship are: (1) embedding a tailor-made approach for inclusive co-production to meaningfully engage diverse actors in place-based settings, (2) embedding open-ended co-production with long-term benefits, and (3) embedding new relations and roles to sustain co-production.
Keywords: Co-production; Collaborative governance; Nature-based solutions; Cities; Capacities; Inclusive Society; International Integration; Smart & Sustainable Planet; CAPACITY; Collaborative governance; GOVERNANCE; LIveable Cities; NATURE-BASED SOLUTIONS; co-production; Communication; Globalization; Social participation